Meningkatkan Kolaborasi dengan Model PBL Murid Kelas IV Fase B SDN 14 Tontang Kabupaten sintang - Yuvinus Sujiman; Galan Suswardana; Hartutik Hartutik (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
Uneven student collaboration and low levels of critical thinking remain challenges for teachers in Grade IV, Phase B at SDN 14 Tontang, Sintang Regency. This study aims to enhance student collaboration through the implementation of the Problem-Based Learning (PBL) model. PBL is grounded in the use of real-world problems as learning anchors that foster positive interdependence, encouraging students to actively construct knowledge through discussion and collective role negotiation. This Classroom Action Research involved 20 students and was conducted over two cycles under the theme “Jesus as the Fulfillment of God’s Promise.” Cycle I focused on “God’s Promise of Salvation in the Scriptures,” while Cycle II emphasized “The Fulfillment of God’s Promise in the Person of Jesus Christ.” Each cycle followed four stages: planning, implementation, observation, and evaluation. Collaboration indicators included equitable active participation, reduced student dependency, and collective negotiation. Data were collected through observations of affective collaboration and written tests measuring cognitive learning outcomes. The findings revealed a significant improvement in collaboration, with active participation increasing from 64.4% in Cycle I to 86.9% in Cycle II. Cognitive learning outcomes also improved, rising from 74.7 to 85.75. These results demonstrate that the PBL model effectively enhances student collaboration by emphasizing affective aspects within the learning process.